(untitled) (Research, Society and Development, 2020)
The cactus family has more than 1.500 species in the world, endemic species occurring throughout the national territory. In natural populations, Cactaceae suffer strong anthropic pressures, which considerably increases their risk of extinction. The objective of the work was to carry out a study on the spatial distribution and population structure of Pilosocereus pachycladus F. Ritter subsp. pernambucoensis (F. Ritter) Zappi and Cereus jamacaru DC. subsp. jamacaru in two Caatinga areas of Agreste in the Paraíba, state, Brazil. The study environments are located at the Instituto Nacional do Semiárido (INSA), Campina Grande,PB state and Sítio Umburana, Bananeiras,PB state. It had been plotted 10 parcels wich 400 m² to each study environment, and all individuals of P. pachycladus subsp. pernambucoensis and C. jamacaru subsp. jamacaru were accounted for. The spatial distribution of species did not show a tendency to group in populations located at INSA. In the populations of Sítio Umburana, the tendency is towards grouping. According to the Payandeh cluster index (Pi), the population and absolute density in the populations of Sítio Umburana is higher when compared to INSA populations. For spatial patterns, in the cactus populations of Sítio Umburana, individuals of both species have a grouped distribution and in INSA populations they have a tendency to not cluster. Factors such as natural or man-made disturbances, environmental conditions and availability of resources, influenced the population structure of P. pachycladus and C. jamacaru.